Corelations of Clinical Features and Findings in Fibromyalgia Patients - Gülcan Gürer,; Ömer Faruk Şendur, (Archives of Rheumatology, 2006)
Objective: Fibromyalgia (FM) is a common disorder with unknown etiology which is characterized by chronic musculoskeletal pain and increased tenderness at standardized tender points. Additional symptoms are fatigue, sleep disturbances, deconditioning and reduced quality of life. In this study, we investigated the clinical features of fibromyalgia and correlations between the symptoms. Patients and Methods: A total of 171 patients with FM (170 female, one male) were included this study . The severity of the pain was recorded with a visual analog scale and verbal pain scale. Fibromyalgia Impact Questionnaire (FIQ) was used to determine the current health status of patients with FM. Pearson correlation test was used as a statistical test. Results: The most common complaints among patients were fatigue in 163 (%95.3), widespread pain in 156 of cases (%91.2), headache in 143 (%83.6), paresthesia in 135 (%78.9), sleep disturbances in 130 (%76), swollen impression in 111 (%64.9), dry mouth in 96 (%56.1), loss in libido in 65 (%38), symptoms referred to irritable bowel syndrome in 63 (%36.8), dysmenorrhea in 55 (%35), Raynaud's phenomenon in 47 (%27.5). Significant correlations were determined between clinical features similiar to the literature on this subject. (Rheumatism 2006; 21: 41-4)